Engineering a conduction-consistent cardiac patch with rGO/PLCL electrospun nanofibrous membranes and human iPSC-derived cardiomyocytes - Tan, Yao; Chen, Ying; Lu, Tingting; Witman, Nevin; Yan, Bingqian; Gong, Yiqi; Ai, Xuefeng; Yang, Li; Liu, Minglu; Luo, Runjiao; Wang, Huijing; Ministrini, Stefano; et al. (Frontiers in Bioengineering and Biotechnology, 2023)
The healthy human heart has special directional arrangement of cardiomyocytes and a unique electrical conduction system, which is critical for the maintenance of effective contractions. The precise arrangement of cardiomyocytes (CMs) along with conduction consistency between CMs is essential for enhancing the physiological accuracy of in vitro cardiac model systems. Here, we prepared aligned electrospun rGO/PLCL membranes using electrospinning technology to mimic the natural heart structure. The physical, chemical and biocompatible properties of the membranes were rigorously tested. We next assembled human induced pluripotent stem cell-derived cardiomyocytes (hiPSC-CMs) on electrospun rGO/PLCL membranes in order to construct a myocardial muscle patch. The conduction consistency of cardiomyocytes on the patches were carefully recorded. We found that cells cultivated on the electrospun rGO/PLCL fibers presented with an ordered and arranged structure, excellent mechanical properties, oxidation resistance and effective guidance. The addition of rGO was found to be beneficial for the maturation and synchronous electrical conductivity of hiPSC-CMs within the cardiac patch. This study verified the possibility of using conduction-consistent cardiac patches to enhance drug screening and disease modeling applications. Implementation of such a system could one day lead to in vivo cardiac repair applications.